Suppression of red rice seed production by herbicides applied to irrigated rice - Agostinetto, Dirceu; Fleck, Nilson Gilberto; Menezes, Valmir Gaedke; Costa, Emerson Luis Nunes (Pesquisa Agropecuaria Brasileira, 2002)
Morphological similarity between red rice and cultivated rice, associated with a prolific seed production by weedy rice and to grain dehiscence with high moisture content, are factors that contribute to its invasion in rice fields. The objective of this research was to investigate the suppression of viable seed production by red rice, with the intent of reducing its seed bank in the soil. With this purpose, field and laboratory experiments were carried out during the growing seasons of 1997/98 and 1998/99, utilizing the non-selective herbicides glyphosate, glufosinate, and paraquat, applied at two times and at two rates, and the growth regulator maleic hydrazide, tested at two times. A control without chemical treatment was included. The rice cultivar tested was IRGA-416, grown in the presence of a high red rice infestation. The chemicals were applied at physiological maturity of cultivated rice. Variables evaluated in red rice were: numbers of stems without panicle, with normal panicles, and sterile ones, spikelets sterility, seed production, seed weight and germination. The herbicides glyphosate, glufosinate, and paraquat can be used selectively in order to suppress red rice seed production when applied during maturity phase of cultivated rice. Adoption of this technology depends on existence of difference between maturity of cultivated and weedy rice, through use of early maturity rice cultivars.